2015
DOI: 10.4137/ijtr.s24412
|View full text |Cite
|
Sign up to set email alerts
|

Method for Evaluation of the Requirements of B-group Vitamins Using Tryptophan Metabolites in Human Urine

Abstract: Tryptophan metabolism is directly involved with B-group vitamins such as vitamin B2, niacin, and vitamin B6, and indirectly with vitamin B1 and pantothenic acid. We evaluated the validity of requirements of B-group vitamins set by the Dietary Reference Intakes for the Japanese (DRI-J). We investigated the fate of dietary tryptophan in 10 Japanese adult men who ate the same diet based on DRI-J during a 4-week study. Vitamin mixtures were administered based on the amounts in the basal diet during weeks 2, 3, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…The presence of KYNA in human urine obtained from adults and children has been repeatedly reported [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] ( Figure 2 b) ( Table S3 ). The urine concentration of KYNA ranges between 4.04 and 22.18 μM in adults.…”
Section: Distribution Of Kynurenic Acidsupporting
confidence: 54%
See 1 more Smart Citation
“…The presence of KYNA in human urine obtained from adults and children has been repeatedly reported [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] ( Figure 2 b) ( Table S3 ). The urine concentration of KYNA ranges between 4.04 and 22.18 μM in adults.…”
Section: Distribution Of Kynurenic Acidsupporting
confidence: 54%
“…The excretion of KYNA in human urine has been repeatedly reported [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ] ( Table S3 ). It can be concluded that the excretion of KYNA in urine ranges from 1.14 to 6.29 mg/day/adult person.…”
Section: Excretion Of Kynurenic Acidmentioning
confidence: 87%
“…Disruption of the one-carbon metabolism could also underlie the inverse association between first trimester maternal 5-HTP and embryonic and fetal growth. TRP metabolism provides one-carbon units for the folate cycle and shares cofactors with one-carbon metabolism, which is crucial for epigenetic programming of cells and tissues ( Steegers-Theunissen et al , 2013 ; Shibata et al , 2015 ). A deficiency of a shared cofactor, for example vitamin B6, can lead to increased 5-HTP and homocysteine concentrations ( Shabbir et al , 2013 ; Steegers-Theunissen et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B6 serves as an illustrative example as it is crucial not only for converting total homocysteine into cystathionine, but also for the conversion of KYN into downstream metabolites and for the conversion of 5-HTP to 5-HT. 10 , 19 , 59 , 60 However, future research is warranted to elucidate the exact mechanism underlying the observed associations, and explore the role of various cofactors in this complex interplay between the tryptophan metabolism and one-carbon metabolism.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 13 - 18 Derangement of the one-carbon metabolism often coincides with disruption of the tryptophan metabolism, as the tryptophan metabolism provides once-carbon units for the folate cycle and shares cofactors with the one-carbon metabolism. 10 , 19 Tryptophan metabolites are involved in redox reactions, and can have pro- and anti-oxidative properties. Disruption of the tryptophan metabolism can induce excessive oxidative stress and subsequent inflammation, which are involved in adverse pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%